2017
DOI: 10.18176/jiaci.0110
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce Allergy Is a Lipid Transfer Syndrome-Related Food Allergy With a High Risk of Severe Reactions

Abstract: Background and Objectives: Lipid transfer protein (LTP) sensitization is the most common cause of food allergy in the Mediterranean area, with peach allergy acting as the primary sensitizer in most cases. Lettuce has been described as a common offending food in patients with LTP syndrome. The aim of the study was to investigate the frequency and clinical expression of LTP syndrome in a sample of lettuceallergic patients. Methods: We determined specific IgE to Pru p 3 and lettuce in a sample of 30 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The major peach allergen is Pru p 3, a nonspecific lipid transfer protein (nsLTP) . NsLTPs are panallergens highly distributed among all plant‐food species, being therefore associated with sensitization to multiple, nontaxonomically related plant‐derived foods, inducing a complex clinical manifestation defined as LTP‐syndrome . This is considered a serious health problem and is increasing in prevalence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major peach allergen is Pru p 3, a nonspecific lipid transfer protein (nsLTP) . NsLTPs are panallergens highly distributed among all plant‐food species, being therefore associated with sensitization to multiple, nontaxonomically related plant‐derived foods, inducing a complex clinical manifestation defined as LTP‐syndrome . This is considered a serious health problem and is increasing in prevalence .…”
Section: Introductionmentioning
confidence: 99%
“…[7] NsLTPs are panallergens highly distributed among all plantfood species, being therefore associated with sensitization to multiple, nontaxonomically related plant-derived foods, inducing a complex clinical manifestation defined as LTP-syndrome. [8] This is considered a serious health problem and is increasing in prevalence. [9] Current treatment is based on the avoidance of peach, however this does not rule out the possibility of accidental ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…26 Even when peach is not the initial reported food trigger, it is still often cited by patients as provoking reactions. 17,28 In other parts of Europe, nsLTP sensitization linked to clinical reactions is reported in an increasing number of publications and the food sensitizations are also similar. A study from Belgium found 25% were sensitized to nsLTP in apple, peach, hazelnut and peanut.…”
Section: Foods Involvedmentioning
confidence: 98%
“…Most individuals with nsLTP allergy are polysensitized to many LTP allergens 17 . It has been described that nearly 90% of adult patients with peanut ( Arachis hypogaea ) allergy in the Mediterranean area are sensitized to Ara h 9, with Pru p 3 being the primary sensitizer, indicating that Pru p 3 sensitization could be a risk factor for developing peanut allergy 107,108 .…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation